2019
DOI: 10.1186/s12866-018-1371-9
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Leptospira by leukocytes from mice with different susceptibility to leptospirosis and possible role of chemokines

Abstract: BackgroundLeptospirosis is a widespread zoonosis caused by pathogenic prokaryotic microbes of the genus Leptospira. Although there are several reports in the literature, host-pathogen interaction is still poorly understood. The role of chemokine expression is important on the chemotaxis, activation and regulation of immune cells. Recent studies have shown that their expression profiles play an important role on the severity of leptospirosis outcome. We evaluated the phagocytosis of Leptospira by spleens cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Macrophages infected with Leptospira have shown that microRNAs (miRNAs) are regulated by infection with the spirochete, demonstrating that this regulation is vitally important in the response of these immune system cells in Leptospira infection [ 66 ]. In human macrophages, the activation of the inflammation mediated by reactive oxygen species and lysosomal cathepsin B generated by Leptospira infection has prominent levels of NLRP3 and IL-18, favoring the production of IL-1 and leading to a high possibility of phagocytosis and the rapid modeling of some cytokines correlated with leptospirosis resistance [ 67 ].…”
Section: Host Immunity Responses To Leptospira Sppmentioning
confidence: 99%
“…Macrophages infected with Leptospira have shown that microRNAs (miRNAs) are regulated by infection with the spirochete, demonstrating that this regulation is vitally important in the response of these immune system cells in Leptospira infection [ 66 ]. In human macrophages, the activation of the inflammation mediated by reactive oxygen species and lysosomal cathepsin B generated by Leptospira infection has prominent levels of NLRP3 and IL-18, favoring the production of IL-1 and leading to a high possibility of phagocytosis and the rapid modeling of some cytokines correlated with leptospirosis resistance [ 67 ].…”
Section: Host Immunity Responses To Leptospira Sppmentioning
confidence: 99%
“…ZG22, symbiotically residing in Dasymaschalon rostratum . Prenylcephalochromin A exhibited an IC 50 of 2.9 mM while for prenylcephalochromin B the value was 2.8 mM for α-glucosidase inhibition when compared to the positive control acarbose (a clinically approved drug) which exhibited an IC 50 value of 2.3 mM (Song et al 2019a ). Another anti-diabetic agent reported was 2,4,6-triphenylaniline (41) which was isolated from Alternaria longipes strain VITN14G existing as a mutualistic symbiont in Avicenna officinalis , a mangrove plant.…”
Section: Pharmaceutically Active Metabolitesmentioning
confidence: 99%